Micro-CT 1172 in Restorative Dentistry - KAMALAK, HAKAN; NUAIMI, HICHAM (Asian Pacific Journal of Health Sciences, 2014)
Micro-computed tomography device, Skyscan 1172, is a product of the new generation. The system in which both the bed of the samples and the camera of X-ray is moving shows the highest level of image resolution. Through computerized tomography, it is possible to obtain information from the object image, to handle cross-sectional images obtained in different ways by editing, to obtain the desired color regions, and to focus on area of interest asnd then remove that area. In this article, after giving information about Micro CT, especially in applications of restorative dentistry; the information has been given about in which areas and with what purpose it can be used. However; it has been explained that whether the use of micro CT alone in the studies done is sufficient or not.